Sharia Review Analysis in Digital Marketing Campaigns: Case Study of Google Adsense and Facebook Ads - Dedy Setiawan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to analyze the sharia perspective on digital marketing campaigns across two major platforms: Google Ads and Facebook Ads. Using a qualitative approach, this study evaluates the extent to which both platforms comply with sharia economic principles, such as fairness, transparency, and openness. The research focuses on algorithm transparency, audience targeting ethics, user data utilization, and ad content alignment with sharia values. The results show that Google Ads offers relatively good transparency in ad performance management, but many novice advertisers struggle to understand the complex algorithmic system. Meanwhile, Facebook Ads excels in data-driven audience targeting capabilities, but poses ethical challenges related to user data management. This study also found that advertisers' lack of understanding of platform policies is a major factor affecting the effectiveness of ad campaigns on both platforms. This research makes a significant contribution to the development of sharia-based digital marketing literacy, particularly by providing practical guidance for advertisers to run ethical campaigns that align with Islamic values. These findings are also expected to serve as a reference for policymakers in developing regulations that support the integration of sharia principles in digital marketing.